Advanced topics in linear algebra weaving matrix problems through the Weyr Form - O'Meara, Kevin C.; Clark, John; Vinsonhaler, Charles I. (New York [u.a.] Oxford University Press, 2011)
Background linear algebra -- The Weyr form -- Centralizers -- The module setting -- Gerstenhaber's theorem -- Approximate simultaneous diagonalization -- Algebraic varieties
Background linear algebra -- The Weyr form -- Centralizers -- The module setting -- Gerstenhaber's theorem -- Approximate simultaneous diagonalization -- Algebraic varieties..
bibliography pages [384] - 389
Keywords: Algebras, Linear